Antropologie van de moderne geschiedwetenschap? - E. Jonker (BMGN: Low Countries Historical Review, 2009)
J. Tollebeek, Fredericq en zonen. Een antropologie van de moderne geschiedwetenschap   The Anthropology of Modern Historiography? Jo Tollebeek’s book about the Belgian historian Paul Fredericq is meant to be an example of ‘the anthropology of modern professional history’. The author believes that this anthropology goes beyond older genres. The traditional historiography focused too heavily on the intellectual content of history writing, whereas the sociology of knowledge only looked at the infrastructure of history as a profession. The post-modern deconstruction of the political role of history writing has become rather reductionistic. The anthropological gaze has to combine all of these points of view and then try to embed them in background information. Does Tollebeek succeed in doing this? We certainly get a rich picture of content, social context and professional practice. The thrills of archival research, the routine of day-to-day academic life, and the (management of) emotional ties within the community of scholars in particular, all come alive. It comes at a price, though. The precision and specificity of micro-history make comparisons within larger frameworks and developments difficult. This macro level makes more selection and simplification inevitable.